The political-interactional images: the case of Aziz Akhannouch's government - Youssef, Ouhssou; Khaoula, Razmi; Ali, Fallous (Cadernos de Educação Tecnologia e Sociedade, 2024)
During each interaction, each of the interactants tries to enhance their image in order to protect their territory. This is closely related to pathos, the impact created can be positive or negative, which determines the process of exchange. Indeed, the politician presents themselves to the public in person (deputies, ministers, etc.) or remotely (the people) as an actor who aims for the public/state interest. Their position in the majority or opposition impacts their discursive chain in the context of valuing the governing self and devaluing the opposing other. This political dichotomy and competition disappear when the issue concerns a common objective, essentially, the question of Moroccan Sahara (the personal territory = the Moroccan territory). Henceforth, to understand the functioning of ethos in a political context, we have opted for a pragmatic analysis, namely interactional pragmatics. Saying and doing are intertwined with the aim of carrying out a performative political action, the set of speech acts constituting the conversation determining on the one hand the praise of the self, on the other hand the intended impact of the production.